2021
DOI: 10.3390/nano11112998
|View full text |Cite
|
Sign up to set email alerts
|

Nonporous, Strong, Stretchable, and Transparent Electrospun Aromatic Polyurea Nanocomposites as Potential Anticorrosion Coating Films

Abstract: This study, for the first time, focused on the fabrication of nonporous polyurea thin films (~200 microns) using the electrospinning method as a novel approach for coating applications. Multi-walled carbon nanotubes (MWCNTs) and hydrophilic-fumed nanosilica (HFNS) were added separately into electrospun polyurea films as nano-reinforcing fillers for the enhancement of properties. Neat polyurea films demonstrated a tensile strength of 14 MPa with an elongation of 360%. At a loading of 0.2% of MWCNTs, the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…This is due to the highly elastomeric property of polyurea, allowing for a rearrangement of the matrix chains after the load is removed. 24 This may have resulted in a redistribution of the stress through the viscoelastic polyurea matrix, resulting in the undeformed sample.…”
Section: Flexural Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…This is due to the highly elastomeric property of polyurea, allowing for a rearrangement of the matrix chains after the load is removed. 24 This may have resulted in a redistribution of the stress through the viscoelastic polyurea matrix, resulting in the undeformed sample.…”
Section: Flexural Propertiesmentioning
confidence: 99%
“…19−21 These studies showed that polyurea can absorb and store significant amounts of energy and reduce shock waves on the composites. 22 Polyurea-infused fibers, however, have never been explored yet due to their fast curing and high viscosity. 23,24 The main goals of the VARTM technique are to achieve a better fiber−resin ratio and less resin utilization and yield good quality products with lesser voids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] At present, the researches on RPU are mainly focused on the improvement of strength and toughness. Researchers have attempted to add different types of reinforcement materials to RPU in order to improve its mechanical properties, such as inorganic particles, 6,7 metal particles, 8,9 fibers 10,11 and organic nanoparticles, 12,13 and so on.…”
mentioning
confidence: 99%